When a neglected tropical disease goes global: early estimates from the Monkeypox outbreak, the first 1,054 cases - Riccò, Matteo (Acta Biomedica Atenei Parmensis, 2022)
Monkeypox virus (MPXV), genus Orthopoxvirus, is a large double-stranded DNA virus (200-250 nm), that is evolutionarily related to human variola virus (VARV) (1), and causes a clinical syndrome quite similar to smallpox, with a generally less severe outcome (1,2).MPXV has a wide range of hosts and reservoirs in wild animals, and since 1970 has been commonly acknowledged as a human pathogen, endemic to Central and Western African countries through two distinctive clades (2,3). Central African clade (CAC) is responsible of the majority of 20,000 incident cases of the last decade, with a case-fatality-ratio of 7-10%, compared to < 4% for Western African clade (WAC) (4).In 2003, the importation of infected pests (Cynomys spp, i.e. “prairie dogs”) to United Stated resulted in the first MPXV-WAC outbreak out of Africa, involving a total of 81 human cases, with no documented deaths (5). In the next decade, the spreading of the MPVX-WAC to Nigeria, has then resulted in multiple travel-related cases in non-endemic countries (4,6).Since May 7th, 2022, an unprecedented outbreak of MPXV-WAC infections with around 1,051 documented cases (Table 1) is occurring across Europe (89.7% of cases), Americas (10.7%), and Australia (0.6%), mostly occurring in subjects with no established travel link to endemic areas (7–13).Reported cases are mostly characterized by mild clinical features (Table 2) (7,9,10,12,13), with no deaths and some specificities. First of all, skin lesions are inconsistently pronounced in number, size and density, being possibly confounded with chickenpox (7,13). Similarly, cervical lymphadenopathy, previously acknowledged as a nearly constant clinical sign, has been reported by less than 20% of incident cases (7,9,13), with an increased prevalence of inguinal lymph node involvement (35.3% to 48.1%) (7,9,13), anal and genital ulcers (18.5% to 57%) (9,10,13).As some cases have been initially reported in men having sex with men (9,14), with a relatively high prevalence of HIV seropositivity (9,10), reporting risky sexual behaviors and multiple sexual partners (9,10,12), and having a documented epidemiologic link with high-risk settings in Madrid and Lisbon areas, and mass gatherings in Antwerp (Belgium), and Gran Canaria (Canary Islands, Spain) (8,9,12,14), such specificities have been initially explained through a presumptive sextually-related transmission. However, labelling the current outbreak as a sort of “gay” disease is not only improper and discriminating, but also scientifically inaccurate (9). First, most of reported cases remain outside a clear and well-defined chain of transmission (9,10,12). Second, the earliest symptom onset clearly ranged between April 20th and April 29th, anticipating all of the aforementioned mass gatherings (9,12). Third, 3 of recent US cases were linked to travel-associated cases from Nigeria reported in 2018 and 2019 (15). In other words, the current MPXV-WAC outbreak has been introduced in Western Hemisphere by several, distinctive episodes that have largely anticipated the initial hypotheses. As its containment of appears, to date, particularly difficult to achieve MPXV-WAC could profit of this outbreak to eventually evolve into a global pathogen (3,14), corroborating a decade of disregarded warning from International Health authorities (2,3).